Oral History and Organizational Research: Challenges of Building Knowledge about the Past - Ayumi Hodge, Patricia; de Sá Mello da Costa, Alessandra (Organizações & Sociedade, 2021)
Oral history has been increasingly used in management research in recent years, bringing to the forefront the view of individuals about past organizational phenomena. However, this use has not yet fully explored the construction of knowledge about the past. Instead, it has focused on studying the present and, therefore, hardly distinguishes oral history from qualitative methods such as case studies and in-depth interviews. How then should we use oral history and its historiography that has made it quite distinctive in history? How should we use individuals’ views to construct new knowledge of the past? This paper addresses these two questions, advocating for the use of oral history both as a theoretical-methodological approach and subfield of history, as well as firmly engaged with historical organizational studies. To that end, we review the trajectory of oral history, then we analyze 16 Brazilian papers on oral history, highlighting the distinctive characteristics of the approach, and, finally, we present research possibilities in historical organizational studies.